2004
DOI: 10.1111/j.1365-2400.2004.00349.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and rehabilitation of the spawning habitats of the sea trout, Salmo trutta, in Gotland (Sweden)

Abstract: Characteristics of the natural spawning habitat of sea trout, Salmo trutta L., were studied in Sja¨lso¨a˚n, a small stream of Gotland, Sweden, from 1992 to 1999. Each year, trout spawned on 17 ± 7 different areas (156 places ha )1 ). Most of the spawning grounds were used every year. Overcutting was evident for at least 60% of the spawning grounds. Fish spawned on a gravel of 19 ± 7 mm in diameter.From 1978 to 1992, 242 artificial spawning grounds were constructed by the Gotland Sport Fishermen Association in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
3
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 15 publications
4
48
3
1
Order By: Relevance
“…A general lack of natural spawning areas most likely contributed to this immediate response. Similar quick responses have also been reported from other studies with addition of spawning gravel for both Atlantic salmon (White, 1942) and brown trout (Rubin et al, 2004).…”
Section: Resultssupporting
confidence: 82%
“…A general lack of natural spawning areas most likely contributed to this immediate response. Similar quick responses have also been reported from other studies with addition of spawning gravel for both Atlantic salmon (White, 1942) and brown trout (Rubin et al, 2004).…”
Section: Resultssupporting
confidence: 82%
“…The coldest temperature was 4.2°C (Table 1), attained on reach 3 only for 2 days and no break was observed. The highest redd density in our study (reach 3) was slightly lower than that reported by Rubin et al (2004) for sea trout (1.56 -reddsAE100 m )2 ). Beard & Carline (1991) reported roughly similar redd densities (0.02-1.06 reddsAE100 m )2 ) to those observed in the Castril (Table 1).…”
Section: Influence Of Stream Flow and Water Temperaturecontrasting
confidence: 80%
“…High variance in sperm quality and sexual competition at high density results in greater variance in individual reproductive success and a greater reduction in the effective size of population (N e ) relative to the census size (N) (Belmar-Lucero et al, 2012). High density of breeders in relation to the loss of suitable spawning grounds increases the risk of red superimposition (McNeil, 1964;Champigneulle et al, 2003;Rubin et al, 2004), further reducing the N e /N ratio (Belmar-Lucero et al, 2012). Moreover, the strong competition of the early stages after emergence results in further loss of population fitness by densitydependent mortality (Milner et al, 2003).…”
Section: Discussionmentioning
confidence: 99%